Can microteaching be used for teaching postgraduate psychiatry residents in a small group?. (June 2016) - Praharaj, Samir Kumar
Objective: The objective of this study was to examine the feasibility of using microteaching for teaching postgraduate psychiatry residents in a small-group setting. Methods: Twelve postgraduate psychiatry residents attending the tutorial program were employed as study participants. Five of the consenting residents took part in the microteaching session in which subtopics were assigned. Feedback was obtained from the presenters and other participants regarding the microteaching session. Results: All of the presenters reported the microteaching session to be helpful in gaining a deeper understanding of the topic. Among the other participants, most found the microteaching exercise to be useful. Conclusion: Although preliminary, our findings suggest that microteaching can be used for training postgraduate psychiatry residents.